2012
DOI: 10.1002/jsfa.5592
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐obesity effect of a standardised ethanol extract from Curcuma longa L. fermented with Aspergillus oryzae in ob/ob mice and primary mouse adipocytes

Abstract: These results suggest that supplementation of FTE has potent anti-obesity effects by controlling body weight, fat mass, serum lipids, and hepatic lipids. Moreover, FTE could be considered a potential resource for the treatment of obesity through its promotion of lipolysis via the protein kinase A pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Animal studies also showed that body weight and adipose tissue decreased with curcumin treatment (Ho et al, ). It seems that turmeric can increase lipolysis via protein kinase‐A pathway (Ho et al, ). Also, curcumin increases fatty acids oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies also showed that body weight and adipose tissue decreased with curcumin treatment (Ho et al, ). It seems that turmeric can increase lipolysis via protein kinase‐A pathway (Ho et al, ). Also, curcumin increases fatty acids oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In Minpei kuroda et al study, 0.2 or 1.0 g/100 g diet (260 and 1,500 mg/kg body weight) of turmeric extract in the diet of diabetic mice for 4 weeks prevented the blood glucose elevation and improved insulin resistance (Kuroda et al, ). In the study of Ho et al, 200, or 500 mg/kg body weight curcumin ethanol extract in the diet of obese mice for 9 weeks led to weight loss and improved lipid profile (Ho et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with our data demonstrating the anti-adipogenic activity of TENE, which leads to reduced lipid accumulation in a cellular model. The data suggest that TENE may act by regulating cellular differentiation, which makes it suitable as a potential therapeutic agent for obesity (Ho et al, 2012;Song & Choi, 2016).…”
Section: Effects Of Tene On Intracellular Lipid Accumulation In 3t3-lmentioning
confidence: 97%
“…When cells were incubated in the presence of a range of concentrations of TENE (0, 1, 2, 5, 10, or 30 μg/mL) for 24 h, a toxic effect of TENE was not observed up to 10 μg/mL; therefore, 10 μg/mL TENE was used in subsequent experiments ( Figure 1A). Because turmeric extract is a potential therapy for obesity (Ho et al, 2012;Septembre-Malaterre et al, 2016), we assessed whether TENE might affect adipogenesis in 3T3-L1 adipocytes. When 3T3-L1 cells were treated with MDO for 8 days, intracellular lipid content was significantly increased, according to Dil Red D staining.…”
Section: Effects Of Tene On Intracellular Lipid Accumulation In 3t3-lmentioning
confidence: 99%
“…Currently, fermented C. longa L. is known to reduce bitterness and harsh taste, improving the flavor and taste and providing an increase of consumption. 7 So far, several pharmacological effects of fermented C. longa, including hepatoprotective 8 and anti-obesity 9 have been reported whereas little is known about the chemical components of fermented C. longa extract. In the present study, five compounds, including one new sesquiterpene (1) were isolated from the fermented C. longa extract by application of various chromatographic methods.…”
mentioning
confidence: 99%